Exclusive breastfeeding during the first 6 months of life as a protective factor for Bronchial Asthma in the pediatric population - Sotelo, Marisa (2020)
Objectives: to determine the relationship between exclusive breastfeeding during the first 6 months of life and bronchial asthma in the pediatric population at the National Police Hospital in 2016.  Materials and methods: an analytical observational study of cases and controls was not matched. ratio 1 case for 3 controls, with a total of 53 cases and 159 controls, a simple random probability sampling was performed, with a retrospective collection for the variables exclusive breastfeeding, Prematurity, sex and age. A bivariate and multiple logistic regression model was performed to obtain the Odds Ratio for the strength of association. Results: being 24.53% and 44.65% exclusive breastfeeding for cases and controls, a statistically significant difference was found (p = 0.009). By multiple logistic regression analysis exclusive breastfeeding (OR 0.41, p = 0.014, IC 0.20-0.84) showed a relationship for bronchial asthma. Conclusions: a relationship was found between exclusive breastfeeding and bronchial asthma which can be extrapolated to the pediatric population of the city of Lima, this is the first article published in this regard at the national level, prospective studies are recommended to determine causality.